The spectrum of language impairments in amyotrophic lateral sclerosis. (November 2020) - Ceslis, Amelia; Argall, Rosemary; Henderson, Robert D.; McCombe, Pamela A.; Robinson, Gail A.
Abstract: Language disorders are increasingly recognised in Amyotrophic lateral sclerosis (ALS), supporting the view of ALS as a multi-system disorder, impacting cognitive and motor function. However, the language impairments are heterogeneous and recent focus has been on determining the language profile across the ALS spectrum with little focus on spontaneous speech. The current study systematically investigated a wide range of language abilities in an unselected ALS sample (N = 22), including spontaneous speech. We analysed the ALS patients' performance as a group, compared to age-, education- and IQ-matched healthy controls (N = 21), and as a case series to identify dementia and specific language profiles. The ALS group was impaired on measures of spontaneous speech, word fluency and action naming. By contrast, object naming, semantic memory (object and actions), sentence comprehension and repetition (word and sentences) were comparable to healthy controls. In line with recent suggestions, our ALS patients' action naming (but not action semantic) deficit does not support the notion that action processing may be selectively impaired in ALS. The case series demonstrated that 14% of patients had probable dementia, 31% showed significant cognitive and/or language impairment and 55% were unimpaired, consistent with the spectrum of cognitive and language impairments reported in the literature. In addition, 36% of ALS patients produced significantly fewer words per minute on a spontaneous speech task than the control group, with this difference remaining when the ALS patients with frontotemporal dementia were excluded from the analysis. This pattern was observed across the ALS spectrum and in both limb and bulbar onset patients. The pattern of performance observed in the present study suggests that spontaneous speech is reduced across the ALS spectrum even in those with intact core language abilities.